Patterns of sedentary time and cardiometabolic risk among Canadian adults - Carson, V.; Wong, S.; Winkler, E.; Healy, Genevieve; Colley, R.; Tremblay, M. (Academic Press Inc., 2014)
Objective: The aim of this study is to examine the associations of total sedentary time and patterns of sedentary time with cardiometabolic biomarkers in a large representative sample of Canadian adults. Methods: The study is based on 4935 adults aged 20-79. years, from the 2007/09 and 2009/11 Canadian Health Measures Survey. Total sedentary time, patterns of sedentary time (=. 20. minute prolonged sedentary bouts, number of sedentary breaks), and moderate- to vigorous-intensity physical activity (MVPA) were accelerometer-derived. Waist circumference, systolic and diastolic blood pressure, high-density lipoprotein (HDL) cholesterol, and C-reactive protein were measured. Triglycerides, low-density lipoprotein (LDL) cholesterol, insulin, and glucose were also measured in a fasting sub-sample (n= 2551). Results: Total sedentary time and time in =. 20. minute prolonged sedentary bouts were associated with higher insulin and lower diastolic blood pressure levels (P<. 0.05). On average, each additional 10 breaks/day was associated with 0.83 (95%CI: 1.35, 0.31) cm lower waist circumference, 0.32 (0.62, 0.02) mm. Hg lower systolic blood pressure, 0.01 (0.00, 0.02) mmol/l higher HDL-cholesterol, 3.72 (1.34, 6.13) % lower triglycerides, 0.57 (0.23, 0.92) % lower glucose, and 4.19 (1.80, 6.63) % lower insulin. Conclusion: These findings in a large representative sample of Canadian adults indicate that breaking up sedentary time may be particularly important for cardiometabolic health. © 2014 Elsevier Inc.